Coil-free active stabilisation of extended payloads with optical inertial sensors. (26th March 2018) - Watchi, J; Ding, B; Tshilumba, D; Artoos, K; Collette, C
Abstract: This paper presents a new active isolation strategy and system which is dedicated to extended payloads, and compatible with the particle accelerator environment. In comparison to the current isolation systems used in this environment, the system proposed does not contain any coil or elastomer, and the supporting frame is dedicated to isolating long payloads from seismic motion. The concept proposed has been tested numerically on 3 and 6 degrees of freedom (DOF) models, and validated experimentally on a 1-DOF scaled test set-up. An attenuation of 40 dB at 1 Hz has been reached with the stage built. The complete description of performance and a noise budgeting are included in this paper.